2022
DOI: 10.3390/mi13081308
|View full text |Cite
|
Sign up to set email alerts
|

Protein Albumin Manipulation and Electrical Quantification of Molecular Dielectrophoresis Responses for Biomedical Applications

Abstract: Research relating to dielectrophoresis (DEP) has been progressing rapidly through time as it is a strong and controllable technique for manipulation, separation, preconcentration, and partitioning of protein. Extensive studies have been carried out on protein DEP, especially on Bovine Serum Albumin (BSA). However, these studies involve the usage of dye and fluorescent probes to observe DEP responses as the physical properties of protein albumin molecular structure are translucent. The use of dye and the fluore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 104 publications
0
4
0
Order By: Relevance
“…The Clausius-Mossotti factor (CMF) is related to the effective polarizability of the particle, E is the root-mean-square value of the applied electric field given by Equation ( 2). 33 The CMF is a unitless number that quantifies the interaction between the particle and medium in terms of their respective complex polarizabilities and determines the F DEP direction. It is written below in its complex form,…”
Section: Dep Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…The Clausius-Mossotti factor (CMF) is related to the effective polarizability of the particle, E is the root-mean-square value of the applied electric field given by Equation ( 2). 33 The CMF is a unitless number that quantifies the interaction between the particle and medium in terms of their respective complex polarizabilities and determines the F DEP direction. It is written below in its complex form,…”
Section: Dep Theorymentioning
confidence: 99%
“… FitalicDEP=2πr3ε0εmReitalicCMFE2 where ε m is the absolute permittivity of the surrounding medium, r is the particle radius. The Clausius‐Mossotti factor (CMF) is related to the effective polarizability of the particle, E is the root‐mean‐square value of the applied electric field given by Equation () 33 . The CMF is a unitless number that quantifies the interaction between the particle and medium in terms of their respective complex polarizabilities and determines the F DEP direction.…”
Section: Dep Theorymentioning
confidence: 99%
“…Characterization of Staphylococcus aureus using DEP for DEP response pDEP, crossover frequency and nDEP in this recent years is important for detection, manipulation and isolation of the cells [3,4]. Based on past research, DEP devices focusing on 80 µm interelectrode gap for biological application [5][6][7][8][9]. In this work, we improvised DEP technique by decreasing interelectrode gap device to 20 µm for characterization of Staphylococcus aureus.…”
Section: Introductionmentioning
confidence: 99%
“…Recently Nasir et al. [42] reported on the protein albumin manipulation and electrical quantification of molecular DEP in bio‐applications.…”
Section: Introductionmentioning
confidence: 99%
“…Turcan and Olariu [32] focused on the electromanipulation and electrical characterization of various cancerous cells. Recently Nasir et al [42] reported on the protein albumin manipulation and electrical quantification of molecular DEP in bio-applications.…”
mentioning
confidence: 99%